Nanocomposite Coatings for Biomedical Applications - Ma, Rong (My University, 2010)
New electrochemical deposition methods have been developed for the fabrication of advanced composite coatings for biomedical applications. The methods are based on electrodeposition of biopolymers, such as cathodic electrodeposition of chitosan, anodic electrodeposition of alginic acid and hyaluronic acid. Another approach is based on anodic electropolymerization of polypyrrole. Electrochemical strategies have been discovered for the electrochemical co-deposition of polymers with other functional biomaterials, such as proteins, drugs, bioactive ceramics and bioglass. Bovine serum albumin was used as a model protein for the development of new electrochemical strategies for the fabrication of composite coatings containing proteins. New strategies have been further utilized for the fabrication of novel composites containing hemoglobin. It was found that biopolymers can be used for efficient electrosteric dispersion of bioceramics and bioglass in suspensions. Co-deposition of biopolymers with bioceramics and bioglass from the suspensions resulted in the fabrication of composite organic-inorganic bone substitute materials.
Electrochemical methods have been developed for the deposition of composite coatings containing functional biomaterials in the matrix of conductive polypyrrole. New additives have been developed for the deposition of polypyrrole on low cost stainless steel substrates. The additives enabled the passivation of the stainless steel substrates and charge transfer during anodic electropolymerization. The composite coatings were obtained as monolayers, multilayers or materials of graded composition.
The composition and microstructure of the composite coatings were investigated. The composition of these nanocomposite coatings can be varied by variation in bath composition for electrodeposition. The deposition yield was studied at various deposition conditions. Electrochemical deposition mechanisms have been investigated and discussed. Obtained results pave the way for the fabrication of novel coatings for the surface modification of biomedical implants and for application in advanced biosensors.
Keywords: Materials Science and Engineering; Materials Science and Engineering